HUBUNGAN MANAJEMEN PENGETAHUAN DENGAN INOVASI : PENGEMBANGAN WISATA PEDESAAN DI DESA PASIR ANGLING SUNTEN JAYA JAWA BARAT INDONESIA - Muhammad Harri; Suharto (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The development of a village into a tourist village is increasingly becoming a trend in the era of the COVID-19 pandemic. Especially village tourism related to nature tourism, agriculture, plantations, heritage sites and culture. It can be said that from the market theory, the village is the supply side and tourists are the demand side. As the supply side, the village continues to grow with the construction of infrastructure, cultural development, and trainings. In the era of modern management, the role of knowledge management and innovation has encouraged villages in Indonesia to realize the village as a tourist village. Thus there will be a multiplier effect to increase the income of rural communities. The research sample is a rural communities and local goverment officials Sunten Jaya village  as many as 150. The methods used are correlation analysis and regression to find out the relationship between knowledge management with innovation to rural tourism development. This paper will examine the relationship of knowledge management with innovation and its implications in the tourist village of Pasir Angling, Sunten Jaya Village, West Java, Indonesia. Besides, this paper also discusses the role of the University in participating in developing tourist villages.